Pengaruh Penyaluran Zakat, PDRB dan Pendidikan terhadap Pengentasan Kemiskinan di Provinsi Yogyakarta Tahun 2016-2022 - mubarokah, merina nurlaili; Pimada, Laila Masruro (ITB AAS INDONESIA Surakarta, 2024)
Poverty is a condition in which a person or group of people is unable to fulfill their basic needs. According to the Central Bureau of Statistics (BPS), in March 2023, the number of poor people in Indonesia amounted to around 25.90 million people, the majority of Indonesia's poor people are on the island of Java. Of the six provinces in Java, Yogyakarta province has the highest percentage of poor people, which is 11.04%. This study aims to analyze how and how much influence the distribution of zakat, GRDP and education level on poverty alleviation in Yogyakarta Province in 2016-2022. Data analysis using panel data regression in 4 regencies and 1 city in Yogyakarta Province for the period 2016-2022. The results showed that the distribution of zakat had no effect on poverty alleviation, GRDP had a negative and significant effect on poverty alleviation, and the level of education had a negative and significant effect on poverty alleviation.